Estimates of abundance of the eastern North Pacific stock of gray whales (Eschrichtius robustus) 1997-2002 - Rugh, David J.; Hobbs , Roderick C.; Lerczak , James A.; Breiwick , Jeffrey M. (J. Cetacean Res. Manage., 2023)
The southbound migration of the eastern North Pacific stock of gray whales (Eschrichtius robustus) was documented by the National Marine Fisheries Service from 13 December 1997 to 24 February 1998, 13 December 2000 to 5 March 2001 and from 12 December 2001 to 5 March 2002. Research protocol was essentially identical to that used in previous surveys. This involved single observers independently searching for whales and recording data on effort and sighting time, location, count and direction-headed. In 1997/98, there were 2,346 pods (3,643 whales) counted during 435.0h of standard observational effort when visibility was recorded as fair to excellent. In 2000/01, a total of 1,694 pods (2,754 whales) were counted during 592.4h, and in 2001/02, there were 1,712 pods (2,800 whales) during 531.5h. The southbound migrations in 1997/98 and 2001/02 were normal, beginning in mid-December, centred on mid-January (mean dates=18 January 1998 and 15 January 2002 respectively) and ending by mid-February. However, in 2000/01 (mean date=25 January 2001) the migration was more protracted than any other migration observed in the past 25 years, with many whales still travelling south three weeks after the typical end date. Data analysis procedures were comparable to those used in previous years, with the exception of a new correction factor for nighttime travel rates. Abundance estimates were 29,758 whales in 1997/98 (CV=10.49%; 95% log-normal confidence interval=24,241 to 36,531), 19,448 in 2000/01 (CV=9.67%; 95% log-normal confidence interval=16,096 to 23,498) and 18,178 in 2001/02 (CV=9.79%; 95% log-normal confidence interval=15,010 to 22,015). The abundance in 1997/98 was the highest estimate made since this project began in 1967/68. It was followed by two much lower estimates – probably related to the high mortality rates observed in 1999 and 2000. This whale population appears to be approaching the carrying-capacity of its environment.